Basalt fiber hybridization effects on the thermal degradation properties of curauá fiber composites. (2020) - Premkumar, T.; Siva, I.; Munde, Yashwant; Rajesh, S.; Amico, Sandro C
Abstract: The use of composite material in engineering application is growing day by day. Researchers have focused on natural fiber composites due to their versatile natures. Present work, the thermal stability of the composites prepared with curauá, basalt and their hybrids into polyester matrix were investigated as a function of hybridization. The composites were prepared by relative percentages of curauá with basalt maintained as 1:1 and length (L) of fibers kept common as 10 mm. Composites were produced through Resin Transfer Molding (RTM) for varying injection and completion pressure. Thermal degradation study was done on a DTGA instrument for temperature ramping. Results reveal that, the onset degradation of pure curauá fiber composite and hybrid composite were due to the cellulose disintegration. The derivative weight curve shows that, incorporation of the basalt fiber sustained the onset degradation to 50 °C due to its inherent thermal resistance nature.